2014
DOI: 10.1175/jamc-d-14-0082.1
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation Estimates from MSG SEVIRI Daytime, Nighttime, and Twilight Data with Random Forests

Abstract: A new rainfall retrieval technique for determining rainfall rates in a continuous manner (day, twilight, and night) resulting in a 24-h estimation applicable to midlatitudes is presented. The approach is based on satellite-derived information on cloud-top height, cloud-top temperature, cloud phase, and cloud water path retrieved from Meteosat Second Generation (MSG) Spinning Enhanced Visible and Infrared Imager (SEVIRI) data and uses the random forests (RF) machine-learning algorithm. The technique is realized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(100 citation statements)
references
References 60 publications
2
94
2
2
Order By: Relevance
“…The modelling methodology follows the study of Kühnlein et al (2014a, b) who used the spectral channels of MSG SE-VIRI to train a random forest model that is able to spatially estimate rainfall areas and rainfall rates over Germany. Based on this study, Meyer et al (2016) have shown that neural networks outperform the initially used random forest algorithm.…”
Section: Model Strategies For Rainfall Estimation 231 General Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The modelling methodology follows the study of Kühnlein et al (2014a, b) who used the spectral channels of MSG SE-VIRI to train a random forest model that is able to spatially estimate rainfall areas and rainfall rates over Germany. Based on this study, Meyer et al (2016) have shown that neural networks outperform the initially used random forest algorithm.…”
Section: Model Strategies For Rainfall Estimation 231 General Modelmentioning
confidence: 99%
“…Kühnlein et al (2014a, b) and Meyer et al (2016) presented a methodology to estimate rainfall from optical Meteosat Second Generation (MSG) Spinning Enhanced Visible and InfraRed Imager (SEVIRI) data for Germany. In this approach, machine learning algorithms were used to relate the spectral properties of MSG to reliable radar data as a ground truth.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it is widely known that correlations between predictions and observations tend to improve with increasing spatial (e.g., [38]) and temporal aggregation (e.g., [36,40,47,54]). We nevertheless decided to focus solely on pixel-based instantaneous rain rates here because they are especially valuable for real-time nowcasting applications, as they can e.g., be used to fill in gaps during radar downtime and cover regions with poor or no radar coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Tapiador et al [52] provide a general overview on satellite-based rainfall estimations by means of neural networks including a discussion about advantages as well as drawbacks of employing such a statistical-learning approach. In addition, the potential of other machine learning techniques such as random forests has been revealed for precipitation detection based on LEO MW [53] as well as for rainfall retrievals based on GEO IR and visible (VIS) channel input data [54]. Meyer et al [40] compare several machine learning algorithms (random forests, artificial neural networks, and support vector machines) and show that the choice of machine learning algorithm only marginally affects the skill of the rainfall retrieval.…”
Section: Introductionmentioning
confidence: 99%
“…The unbalanced categories in the dependent variable can cause the prediction error between categories also to be unbalanced in random forests modeling [35,47]. Therefore, stratified sampling was used to down-sample the majority category, which has been demonstrated to work better than over-sampling the minority category [48].…”
Section: Samplingmentioning
confidence: 99%